Complying with Europe : EU harmonisation and soft law in the member states - Falkner, Gerda (Themes in European governance., 2005)
What does EU law truly mean for the member states? Do they abide or don't they, and why? This book presents the first encompassing and in-depth empirical study of the effects of 'voluntaristic' and (partly) 'soft' EU policies in all 15 member states.